2016
DOI: 10.1051/0004-6361/201526946
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of different SNLS3 light-curve fitters on cosmological consequences of interacting dark energy models

Abstract: We explore the cosmological consequences of interacting dark energy (IDE) models using the SNLS3 supernova samples. In particular, we focus on the impacts of different SNLS3 light-curve fitters (LCF; referred to in this paper as SALT2, SiFTO and combined sample). Firstly, making use of the three SNLS3 data sets, as well as the Planck distance priors data and the galaxy clustering data, we constrain the parameter spaces of three IDE models. Then, we study the cosmic evolutions of Hubble parameter H(z), decelera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 90 publications
0
13
0
Order By: Relevance
“…It should be mentioned that, previous studies on the SNLS3 datasetWang & Wang (2013a) and JLA datasetLi et al (2016) found strong evidence for the redshift-dependence of color-luminosity parameter β, and this conclusion has significant effects on parameter estimation of various cosmological models;;;;Wang, Wen & Li (2016). In addition, different light-curve fitters of SNIa can also affect the results of cosmologyfitsBengochea (2011); Mohlabeng & Ralston (2013);Hu et al (2016). But in this work, for simplicity, we just adopt the most mainstream recipe of processing SNLS3 data, and do not consider the factors of time-varying β and different light-curve fitters.…”
mentioning
confidence: 90%
“…It should be mentioned that, previous studies on the SNLS3 datasetWang & Wang (2013a) and JLA datasetLi et al (2016) found strong evidence for the redshift-dependence of color-luminosity parameter β, and this conclusion has significant effects on parameter estimation of various cosmological models;;;;Wang, Wen & Li (2016). In addition, different light-curve fitters of SNIa can also affect the results of cosmologyfitsBengochea (2011); Mohlabeng & Ralston (2013);Hu et al (2016). But in this work, for simplicity, we just adopt the most mainstream recipe of processing SNLS3 data, and do not consider the factors of time-varying β and different light-curve fitters.…”
mentioning
confidence: 90%
“…The possible redshift-dependence of the intrinsic scatter σint[80], as well as different choice of SN light-curve fitters[81,82], may also cause the systematic uncertainties of SNIa.…”
mentioning
confidence: 99%
“…It should be mentioned that, the intrinsic scatter σ int also has the hint of redshift-dependence[35] that will significantly affect the results of cosmology-fits. In addition, different light-curve fitters of SN can also affect the results of parameter estimation[36,37]. But in this work, we do not consider these factors for simplicity.…”
mentioning
confidence: 99%